PENGEMBANGAN MEDIA AUDIO VISUAL DENGAN ANIMASI BERBASIS CANVA PADA PESERTA DIDIK KELAS VI SD - ; Jusra, Hella (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2022)
The era of the Industrial revolution 4.0 encourages improvements in almost all aspects, especially changes in the field of education. One of the challenges faced by the education sector is the implementation of Information and Communication Technology or it can be abbreviated as ICT which plays a role in digital-based learning media for students. Canva is an application that supports learning media to be more effective and interesting. This research aims to develop audio-visual media with animation using the Canva application on the solar system material for class VI SD. The research method used by the researcher is the Research and Development (R&D) method and utilizes the 4D development model. Researchers used questionnaires, observations and hearings. The researcher used 26 elementary school sixth grade students as the research sample. The results of the media feasibility test obtained a number of 86% got a very decent category then the material test a number of 84% got a very decent category. In addition, of the students who included cognitive tests and media assessments, 87% and 88% respectively were obtained. In conclusion, Canva-based audio-visual media is able to support learning materials to be more effective and interesting for students.